Pendidikan Islam Berbasis Paradigma Wasathiyyah dan Ummatan Wasathan - Rahmadi, Rahmadi; Hamdan, Hamdan (FENOMENA, 2024)
This study explores the wasathiyyah paradigm, the concept of ummatan wasathan, and the balance within Islamic teachings in the context of Islamic education. It employs a library research method, drawing on relevant literature as the primary source. The findings indicate that the wasathiyyah and ummatan wasathan educational paradigm constitutes a framework comprising concepts, principles, values, theories, methods, and applications upheld by Muslim scholars, rooted in the ideals of moderation. This paradigm seeks to shape a moderate society by internalising wasathiyyah values through education. Islamic education based on this paradigm promotes religious balance between reason and revelation, text and context, worldly and spiritual orientation, divinity and humanity, individual and social life, body and soul, remembrance and reflection, and knowledge and action.